(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To study the co-relation between SOFA score on admission and 48 hours and its outcome in critically ill geriatric patients in Medical Intensive Care Unit. Materials and Methods: The present prospective observational study was conducted on 100 patients of age 60 years and above with dysfunction of at least two organ systems, admitted in medical intensive care unit of Dr DY Patil Medical College Hospital and Research Centre, Pimpri, Pune during the period from OCTOBER 2020– SEPTEMBER 2022. The study was carried out on a total of one hundred patients who fulfilled the qualifying requirements and were admitted to the hospital's medical intensive care unit. Every single one of our patients gave their consent after receiving adequate information. A comprehensive clinical examination, which included both general and physical examinations, was performed on each and every patient. Assessment of the patient's degree of consciousness as well as their score on the Glasgow coma scale were taken at the time of admission for each patient. The severity of an issue is graded according to the GCS as follows: severe (GCS score of 8), moderate (GCS score of 9–12), and mild (GCS score of 13 or lower) (GCS score of 13–15). Patients were monitored during their time in the hospital, and the staff kept a record of the patients' final status—whether they had passed away or had survived. Results: In the present study, out of total 31 mortalities; maximum death (n = 22) reported in 60-69 years of age followed by 70-79 years (n = 9). The mortality was significantly higher in males in comparison with the females. The overall survived female patients were 31 and 38 in males. On analysis significant difference was observed between for the mean values of SOFA score at admission and 48 Hr. among survived and died patients (5.2609±2.95880 and 6.7742±3.98087, p = 0.034) and (4.4928±2.52996, 10.0000±4.29729, p=0.001). On analysis significant difference was observed between for the mean values of Delta SOFA score among survived and died patients (-0.5942±2.28369 and 2.8387±3.08865, p = 0.001). Conclusion: The SOFA score at admission and 48 hours has shown statistically significant association with the outcome of critically ill elderly patients.